2007
DOI: 10.1007/s00425-007-0538-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of asexual reproduction in Nannochloris bacillaris and Marvania geminata (Chlorophyta, Trebouxiophyceae)

Abstract: Non-flagellated vegetative green algae of the Trebouxiophyceae propagate mainly by autosporulation. In this manner, the mother cell wall is shed following division of the protoplast in each round of cell division. Binary fission type Nannochloris and budding type Marvania are also included in the Trebouxiophyceae. Phylogenetic trees based on the actin sequences of Trebouxiophyceae members revealed that the binary fission type Nannochloris bacillaris and the budding type Marvania geminata are closely related in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…However, the latter strains displayed distinct cell morphologies: Nannochloris sp. SBL1 cells were rod-shaped, showing some similarity to Nannochloris bacillaris [16], whereas Nannochloris sp. SBL4 presented rounded or slightly oval cells, as commonly found in this genus.…”
Section: Identification Of Strains By 18s Rdna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the latter strains displayed distinct cell morphologies: Nannochloris sp. SBL1 cells were rod-shaped, showing some similarity to Nannochloris bacillaris [16], whereas Nannochloris sp. SBL4 presented rounded or slightly oval cells, as commonly found in this genus.…”
Section: Identification Of Strains By 18s Rdna Sequencingmentioning
confidence: 99%
“…These values are in accordance with the European standard EN14214 [22], which states a maximum of 12% for α-linolenic acid and 1% for PUFA with ≥4 double bonds. Regarding the size of the carbon chain, isolates displayed a FAME profile ranging from C 15 to C 18 , dominated by C 16 and C 18 FAME. These main FAME are the same that compose soy biodiesel [23], proving the suitability of the FAME profile of these isolates for biodiesel production.…”
Section: Total Lipid Content and Fatty Acid Profilementioning
confidence: 99%
“…In Marvania, by contrast, the "bud" that grows out through the break in the mother cell wall is just an expanding part of the cell residing in the remnant of the mother cell wall; the whole expanding protoplast is enclosed in a newly deposited cell wall and mitosis and subsequent cell division (by means of eleutheroschisis, i.e. deposition of yet another cell wall layer) occurs only when the "bud" is of about the size of the "mother cell" (hiNdák 1976, REymoNd et al 1986, sluimaN & REymoNd 1987, yamamoto et al 2007). Next, in Pseudomarvania, the daughter cell that "buds off" is much smaller than the mother cell (haNda et al 2003, NEustupa & šEjNohová 2003, whereas in Marvania the two cells are of approximately equal size when their separation takes place (hiNdák 1976, REymoNd et al 1986, sluimaN & REymoNd 1987.…”
Section: Discussionmentioning
confidence: 99%
“…The "bud" keeps expanding and when it reaches the dimensions of the part of the cell retained in the remnant of the mother cell wall, two separate cells are formed. Ultrastructural investigations of dividing M. geminata cells revealed that the "budding" is a highly modified form of autosporulation (REymoNd et al 1986, sluimaN & REymoNd 1987, yamamoto et al 2007) designated as semi-exogenous autosporogenesis (sluimaN & REymoNd 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Using sequence comparisons most of our isolates were closely related to those of various other inland freshwaters (Supplementary Table 3). Within the Trebouxiophyceae, these were members of the Chlorellales clade, i.e., Chlorella (Bock et al 2010;Bock et al 2011), Muriella (Fawley et al 2004 and Marvania (Fawley et al 2004;Yamamoto et al 2007). Within the Chlorophyceae, at least the Scenedesmaceae, Selenastraceae and Mychonastes, which we also retrieved in our study, are well known from freshwaters Bock 2012).…”
Section: Species Identification and Originsmentioning
confidence: 99%